Simons, G. y Hofmann, S. G.(2013). CBT for anxiety disorders: A practitioner book.Chichester (UK): Wiley-Blackwell. - Chorot, Paloma (Revista de Psicopatología y Psicología Clínica, 2014)
Simons, G. y Hofmann, S. G.(2013). CBT for anxiety disorders: A practitioner book.Chichester (UK): Wiley-Blackwell. 258 + x pp.